Water Supply and Water Scarcity - Tzanakakis, Vasileios; Paranychianakis, Nikos; Angelakis, Andreas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Book includes selected papers that has been published in the Water journal Special Issue (SI) on Water Supply and Water Scarcity. Moreover, an overview of the SI is included. The papers selected for publication in the SI include review and research papers on water history, on water management issues under water scarcity regimes, on rainwater harvesting, on water quality and degradation, and on climatic variability impacts on water resources. Overall, the issue identify and highlight the main challenges in water sector, and particularly in management and protection of water resources and in use of alternative (non-conventional) water resources, especially in areas with demographic change and climate vulnerability in order to achieve sustainable and secure water supply. Furthermore, general guidelines and possible solutions for an improved and sophisticated water management system are proposed and discussed, such as the adoption of advanced technological solutions and practices that improve water-use efficiency and the use of alternative water resources, to address the growing environmental and health issues and to reduce the emerging conflicts among water users.